2012
DOI: 10.1111/j.1477-9552.2012.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Organic and Conventional Produce in London, UK: A System Approach

Abstract: The majority of studies on consumer demand for organic products neglect the presence of non-organic competitors, ignoring their effect on consumer demand for organics. This article uses a demand system which includes both organic and non-organic fruits and vegetables, with actual (as opposed to stated) data for household purchases. Estimation of our model provides empirical evidence on the interrelationships between organic and non-organic products, as the relevant cross-price elasticities. Own-price elasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…However, the degree to which prices of organic products influence purchase behavior is controversial, i.e., if consumers’ reaction is elastic or inelastic. The majority of studies have found that the demand for organic food is somewhat price elastic (Anders and Moeser, 2008) and in general, more price sensitive than for conventional food (Glaser and Thompson, 2000; Lin et al ., 2009; Alviola and Capps, 2010; Fourmouzi et al ., 2012; Kasteridis and Yen, 2012; Schröck, 2013) which is often attributed to the high-price premiums of organic products and their still minor market share. According to these findings, price reductions of organic food would lead to a revenue increase, as the change in price could be compensated by higher purchase quantities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the degree to which prices of organic products influence purchase behavior is controversial, i.e., if consumers’ reaction is elastic or inelastic. The majority of studies have found that the demand for organic food is somewhat price elastic (Anders and Moeser, 2008) and in general, more price sensitive than for conventional food (Glaser and Thompson, 2000; Lin et al ., 2009; Alviola and Capps, 2010; Fourmouzi et al ., 2012; Kasteridis and Yen, 2012; Schröck, 2013) which is often attributed to the high-price premiums of organic products and their still minor market share. According to these findings, price reductions of organic food would lead to a revenue increase, as the change in price could be compensated by higher purchase quantities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous efforts to measure the price elasticity of demand for organic produce have produced inconsistent results. A London-area study found own-price elasticities for organic fruit and vegetables were approximately three times higher than for conventional ones (Fourmouzi et al 2012; also see Kasteridis and Yen 2012 for similar US results from 2006). An estimate of Dutch consumers' price elasticity of demand for several vegetables found the expected negative signs but never found elastic demand (Bunte et al 2010).…”
Section: Previous Price Elasticity Estimatesmentioning
confidence: 91%
“…As to cross-price elasticities between organic and conventional produce, Fourmouzi et al (2012) found they were low, especially for devoted or frequent organic buyers. Bezawada and Pauwels (2013) found that reductions in organic product prices hurt conventional product sales more than vice versa.…”
Section: Previous Price Elasticity Estimatesmentioning
confidence: 96%
“…Second, the Double-Log estimation of demand provides only a very rough indication of the marginal effect of a price change on the quantity consumed. Due to this and other shortcomings, an Almost Ideal Demand System (AIDS) a la Deaton and Muellbauer (1980), which has become common practice in such estimations (Fourmouzi et al, 2012), was also estimated. In this model, the demand equations for n goods can be expressed as a system of expenditure share equations:…”
Section: Methodsmentioning
confidence: 99%